Fertility status and phosphorus loss risk of vegetable field soils in Xitiaoxi watershed - GUO Xiaoying; LIU Xiaoxia; WANG Jian; NI Yuemin; LENG Mingzhu; NI Wuzhong (浙江大学学报. 农业与生命科学版)
The high degree of intensive utilization of vegetable field soils is prone to nutrient imbalance and excessive accumulation, which hinders the sustainable development of vegetable production. Based on the analysis of fertility status and main obstacle factors of vegetable field soils under the open land and facility cultivation patterns in the Xitiaoxi watershed, the threshold of soil phosphorus (P) loss was explored in this study. The results indicated that the soil pH value under the open land cultivation pattern was significantly lower (P＜0.05) than that under the facility cultivation pattern. The contents of soil total potassium (K), available K, available P, and water-extractable P under the facility cultivation pattern were significantly higher (P＜0.05) than those under the open land cultivation pattern, as well as the total soluble salt content and electrical conductivity. It was also found that the fertility grades of vegetable field soils under the two cultivation patterns were mostly (95.8%) Grade Ⅱ. The correlation between soil water-extractable P and Mehlich 3-P was well illustrated with the piecewise linear regression equation. The threshold of Mehlich 3-P for controlling P loss from the open land and facility vegetable field soils was estimated to be 102.7 mg/kg and 128.7 mg/kg, respectively. Thus, the soil samples exceeding this threshold accounted for 65.0% and 83.3% of the total number of samples, respectively. In conclusion, the soil acidification and the risk of P loss under the open land and facility cultivation patterns in the Xitiaoxi watershed are serious, and the soil salinization under the facility cultivation pattern is an outstanding issue.